Odessa magazine "Theatre" (1922): genesis, genre system, content - ХОЛОД, Ганна (Видавничо-поліграфічний центр “Київський університет”, 2025)
Background. The introduction of the NEP (New Economic Policy) contributed to the activation of artistic processes that required theoretical understanding, as reflected in periodicals of the 1920s. Theatre magazines of this period became platforms for discussing theatrical trends and shaping the cultural discourse of the day. One such magazine was the Odessa publication "Theatre", which requires thorough scientific research. The purpose of the article is to clarify the genesis, highlight the genre system, and examine the content of the journal "Theatre" (Odessa, 1922). To achieve this, the text and visual content of the Odessa journal "Theatre" for 1922 were analysed. Methods. The study used the descriptive method, the method of analysis, synthesis, and generalisation. Results. 4 issues of the journal "Theatre", published in 1922, were analysed, including the text and visual content of the publication. It was found that the journal "Theatre" covered not only theatrical but also cinematic topics. Information about cinema was presented minimally, due to the magazine's orientation towards theatre-related content, as evidenced by its name, and also due to the lack of active development of Ukrainian cinema in 1922. Conclusions. Despite the difficult conditions of its existence, the magazine "Theatre" was a centre of unity for the creative and intellectual community and played a significant role in the formation of theatrical critical thought. This is evidenced by the variety of genres through which theatrical topics were covered in the publication. At the same time, cinematic topics occupied a secondary place and were represented mainly in the form of short information messages and film advertisements. The content of the magazine "Theatre" had a distinctly text-centric nature and was structured according to headings with different names; the visual component was minimal and limited to three photographs and one drawing.

Вступ. Розгортання НЕПу (нової економічної політики) сприяло активізації мистецьких процесів, які потребували теоретичного осмислення в періодичних виданнях 20-х років ХХ століття. Театральні журнали цього періоду стали інформаційними майданчиками для обговорення театральних тенденцій, формуючи культурний дискурс доби. Одним із таких журналів стало одеське видання "Театр", яке потребує ретельного наукового дослідження. Мета статті полягає в з'ясуванні генезису, висвітленні жанрової системи, контенту журналу "Театр" (Одеса, 1922). Для її досягнення було проаналізовано текстовий та зображальний контент одеського журналу "Театр" за 1922 рік. Методи. Під час дослідження було використано описовий метод, метод аналізу, синтезу, узагальнення. Результати. Було проаналізовано 4 номери журналу "Театр", який друкувався 1922 року, зокрема текстовий і зображальний контенти видання. З'ясовано, що в журналі "Театр" висвітлювалася не тільки театральна, а й кінематографічна тематика. Інформацію про кіно було представлено мінімально у зв'язку з орієнтацією журналу на контент, пов'язаний із театром, про що свідчить його назва, а також через відсутність активного розвитку української кінематографії 1922 року. Висновки. Попри складні умови існування, журнал "Театр" був осередком творчої та інтелектуальної спільноти й відігравав важливу роль у становленні театральної критичної думки. Про це свідчить різноманіття жанрів, за допомогою яких у виданні висвітлювалася театральна тематика. Кінематографічна тематика посідала другорядне місце й репрезентувалася переважно у формі заміток і реклам фільмів. Контент журналу "Театр" мав виразно текстоцентричний характер і структурувався за рубриками з різними назвами, візуальний компонент був мінімальним й обмежувався трьома фотографіями й одним малюнком.
Одеський журнал "Театр" (1922): генезис, жанрова система, контент
Keywords: жанри; журнал "Театр"; зображальний контент; кінематографічна тематика; театральна тематика; текстовий контент; genres; magazine "Theatre"; pictorial content; cinematic topics; theatrical topics; text content